2013
DOI: 10.1590/s0103-84782013000700008
|View full text |Cite
|
Sign up to set email alerts
|

Temperatura inicial de germinação no desempenho de plântulas e mudas de tomate

Abstract: RESUMO A produção de mudas é uma das etapas fundamentais para o cultivo do tomateiro e pode ser infl uenciada pela ABSTRACTSeedling production is an important step for the tomato production and can be infl uenced by the initial temperature of germination. The aim of this study was to evaluate the effect of this factor in the tomato germination and seedling growth. It was used four seed lots which were tested for germination, accelerated aging and electrical conductivity to evaluate the physiological potential.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
5
1
5
Order By: Relevance
“…reduced the vigor of the lettuce seeds. Only the Everglades cultivar showed greater tolerance to the thermal stress of the room; however, from 90 storage days, a reduction of its emergence is observed at temperatures of 25 and 35 o C. Similar results were observed by Ferreira et al (2013), according to whom, the temperature of 33 o C affected the emergence and emergence speed of tomato seedlings. This is due to the fact that these temperatures affect the reorganization speed of cellular membranes, affecting the metabolism of the seeds and, thus, reducing the emergence speed of the seedlings.…”
Section: Resultssupporting
confidence: 75%
“…reduced the vigor of the lettuce seeds. Only the Everglades cultivar showed greater tolerance to the thermal stress of the room; however, from 90 storage days, a reduction of its emergence is observed at temperatures of 25 and 35 o C. Similar results were observed by Ferreira et al (2013), according to whom, the temperature of 33 o C affected the emergence and emergence speed of tomato seedlings. This is due to the fact that these temperatures affect the reorganization speed of cellular membranes, affecting the metabolism of the seeds and, thus, reducing the emergence speed of the seedlings.…”
Section: Resultssupporting
confidence: 75%
“…The amount of water/solution absorbed by the seeds for each treatment was calculated by weight difference. The hydration curves were constructed and the appropriate period at which to interrupt the procedure was determined to investigate the effect of seed priming (FERREIRA et al, 2013).…”
Section: First Stepmentioning
confidence: 99%
“…In the 'Mariana' hybrid tomato plant, Ferreira et al (2013) found that temperatures higher than 30 ºC led to greater water uptake by seeds in comparison to the control treatment (20-30 °C), and uptake was faster in the first 25 h, determining this period as the first phase of germination. After this period, stabilization of seed moisture content was observed, characterizing it as phase II of germination.…”
Section: Resultsmentioning
confidence: 92%